Web Application Based Food Ordering and Sales in Campus Environment - Teuku Muharam Rizqullah; Sangajik Suryo Guritno; Naurah Hikmah Aulia (CV. Rayyan Dwi Bharata, 2023)
We developed a Web Application-based Ordering and Sales System within the campus environment to facilitate the ordering and sales process. Our goal is to provide convenience to admins, users and customers with guaranteed access rights. The food menu list is clearly displayed to make it easier for users to place orders online. Customers can easily order food online without having to come to the location, and transactions can be made anytime and anywhere. Our Web Application development uses programming languages such as CSS, HTML, and PHP. Direct surveys were also conducted for research development. Our hope is to provide a better experience for users, admins and customers and keep customer data secure. The development of a Web Application-based Ordering and Sales System aims to provide convenience and comfort to admins, users and customers in making the process of ordering food online and ensuring data security from users.